Effect of different types of active biodegradable films containing lactoperoxidase system or sage essential oil on the shelf life of fish burger during refrigerated storage. (January 2020) - Ehsani, Ali; Hashemi, Mohammad; Afshari, Asma; Aminzare, Majid; Raeisi, Mojtaba; Zeinali, Tayebeh
Abstract: The present study aimed to control the spoilage of fish burger of common carp meat kept at refrigerated temperature (4 ± 2 °C) during 20 days storage using active biodegradable films containing lactoperoxidase system (LPS) or sage essential oil (SEO). Fish burgers were prepared from minced common carp meat and were wrapped in chitosan (CH), alginate (AL) and gelatin (ZH) films containing SEO or LPS. Different groups were kept in the refrigerated temperature and samples taken at day 0, 5, 10, 15 and 20 of storage time for determination of Total Viable Count (TVC), psychrotrophic bacterial count (PTC), Pseudomonas spp. (PSC) and Shewanella spp (ShC). Also, TBARS, pH and sensory properties of the groups were checked during refrigeration. Chitosan films containing LPS were the most effective package to significantly suppress the increase of TVC, PTC, Pseudomonas spp. and Shewanella spp and TBARS during 20-day storage at refrigerated condition compared with other treatments ( P<0.05 ). Moreover, the alginate and chitosan films containing LPS and SEO had the higher ultimate pH ( P<0.05 ). The results of this study indicated that the chitosan film containing LPS extend the shelf life of fish burgers in comparison by other treatments and control for 5 days. Highlights: Chitosan films containing LPS were the most effective package to suppress TVC. Pseudomonas spp. and Shewanella spp. were significantly lower than control. Alginate and gelatin films with LPS significantly reduced the number of TVC and PTC.